The employment of Łódź University tourism and recreation graduates: A sociological analysis - Żulicki, Remigiusz (Turyzm/Tourism, 2017)
This article is focused on selected aspects of the economic ‘fate’ of Tourism and Recreation graduates of the University of Łódź (UŁ). Its aim is to seek answers to the question: ‘What determines graduate employment?’ Surveys conducted by the Career Office of University of Łódź among graduates one year after graduation in 2014, 2015 and 2016 are the empirical basis. Tourism and Recreation graduates were compared with others from the Faculty of Geographical Sciences UŁ. The logistic regression technique was used to predict the status of graduate employment based on independent variables. The strongest predictors of graduate employment were structural and institutional characteristics. The quantitative results were interpreted in the context of the modern role of universities.